Temporal patterns of cancer burden in Asia, 1990–2019: a systematic examination for the Global Burden of Disease 2019 study - Rajesh, Sharma (2024)
BackgroundCancers represent a challenging public health threat in Asia. This study examines the temporal patterns of incidence, mortality, disability and risk factors of 29 cancers in Asia in the last three decades. MethodsThe age, sex and year-wise estimates of incidence, mortality, and disability-adjusted life years (DALYs) of 29 cancers for 49 Asian countries from 1990 through 2019 were generated as a part of the Global Burden of Disease, Injuries and Risk Factors 2019 study. Besides incidence, mortality and DALYs, we also examined the cancer burden measured in terms of DALYs and deaths attributable to risk factors, which had evidence of causation with different cancers. The development status of countries was measured using the socio-demographic index. Decomposition analysis was performed to gauge the change in cancer incidence between 1990 and 2019 due to population growth, aging and age-specific incidence rates. FindingsAll cancers combined claimed an estimated 5.6 million [95% uncertainty interval, 5.1–6.0 million] lives in Asia with 9.4 million [8.6–10.2 million] incident cases and 144.7 million [132.7–156.5 million] DALYs in 2019. The age-standardized incidence rate (ASIR) of all cancers combined in Asia was 197.6/100,000 [181.0–214.4] in 2019, varying from 99.2/100,000 [76.1–126.0] in Bangladesh to 330.5/100,000 [298.5–365.8] in Cyprus. The age-standardized mortality rate (ASMR) was 120.6/100,000 [110.1–130.7] in 2019, varying 4-folds across countries from 71.0/100,000 [59.9–83.5] in Kuwait to 284.2/100,000 [229.2–352.3] in Mongolia. The age-standardized DALYs rate was 2970.5/100,000 [2722.6–3206.5] in 2019, varying from 1578.0/100,000 [1341.2–1847.0] in Kuwait to 6574.4/100,000 [5141.7–8333.0] in Mongolia. Between 1990 and 2019, deaths due to 17 of the 29 cancers either doubled or more, and 20 of the 29 cancers underwent an increase of 150% or more in terms of new cases. Tracheal, bronchus, and lung cancer (both sexes), breast cancer (among females), colon and rectum cancer (both sexes), stomach cancer (both sexes) and prostate cancer (among males) were among top-5 cancers in most Asian countries in terms of ASIR and ASMR in 2019 and cancers of liver, stomach, hodgkin lymphoma and esophageal cancer posted the most significant decreases in age-standardized rates between 1990 and 2019. Among the modifiable risk factors, smoking, alcohol use, ambient particulate matter (PM) pollution and unsafe sex remained the dominant risk factors between 1990 and 2019. Cancer DALYs due to ambient PM pollution, high body mass index and fasting plasma glucose has increased most notably between 1990 and 2019. InterpretationWith growing incidence, cancer has become more significant public health threat in Asia, demanding urgent policy attention and guidance. Its heightened risk calls for increased cancer awareness, preventive measures, affordable early-stage detection, and cost-effective therapeutics in Asia. The current study can serve as a useful resource for policymakers and researchers in Asia for devising interventions for cancer management and control. FundingThe GBD study is funded by the Bill and Melinda Gates Foundation.